Extraction of Cellulose-Based Polymers from Textile Wastes - Felgueiras, Helena P.; Padrão, Jorge; Antunes, Joana C. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The extraction and exploration of cellulose-based polymers is an exciting area of research. For many years, wood (especially from bleached kraft wood pulp) was considered the main source of cellulosic compounds because of its abundance in nature. However, in the past decade, researchers have been devoted to finding alternatives to extract cellulose from byproducts of agricultural crops and/or textile wastes, which are both highly available at a very reduced raw material cost. This book brings together original research that details the recent progresses and new developments in this field, and how this research is contributing to a circular economy.